Triatomine bugs, their microbiota and Trypanosoma cruzi: asymmetric responses of bacteria to an infected blood meal. Issue 1 (December 2016) - Díaz, Sebastián; Villavicencio, Bianca; Correia, Nathália; Costa, Jane; Haag, Karen
Abstract Background Triatomine bugs (Hemiptera: Reduviidae) are vectors of the flagellateTrypanosoma cruzi, the causative agent of Chagas disease. The study of triatomine gut microbiota has gained relevance in the last years due to its possible role in vector competence and prospective use in control strategies. The objective of this study is to examine changes in the gut microbiota composition of triatomines in response to aT. cruzi -infected blood meal and identifying key factors determining those changes. Results We sampled colony-reared individuals from six triatomine vectors (Panstrongylus megistus, Rhodnius prolixus, Triatoma brasiliensis, T. infestans, T. juazeirensis andT. sherlocki ) comparing experimentallyT. cruzi strain 0354-challenged and non-challenged insects. The microbiota of gut and gonad tissues was characterized using high throughput sequencing of region V3-V4 of bacterial 16S rRNA gene. The triatomine microbiota had a low intra-individual diversity, and a high inter-individual variation within the same host species.Arsenophonous appeared as the dominant triatomine bacterial symbiont in our study (59% of the total 16S coverage), but there were significant differences in the distribution of bacterial genera among vectors. InRhodnius prolixus the dominant symbiont wasPectobacterium . Conclusions Trypanosoma cruzi -challenge significantly affects microbiota composition, with challenged vectors harbouring a significantly more diverse bacterial community, both in the gut and the gonads. Our results show that blood-feeding withT. cruzi epimastigotes strongly affects microbiota composition in a species-specific manner. We suggest that triatomine-adapted enterobacteria such asArsenophonus could be used as stable vectors for genetic transformation of triatomine bugs and control of Chagas disease.